Methods in DNA amplification - Rolfs, Arndt; Weber-Rolfs, Ines; Finckh, Ulrich; International PCR Symposium on Usage of PCR and Alternative Amplification Methods in Infectious and Genetic Diseases (2nd : 1993 : Berlin, Germany) (New York : Plenum Press, 1994)
42